Pemanfaatan Arabic Pad Untuk Penulisan Bahasa Arab Pada DKM Masjid Jami Darul Hikmah - Evy Priyanti; Veti Apriana; Raden Mohammad Riezky Pahlevi; Dwiyanto Kuncoro (Jurnal Abdimas Komunikasi dan Bahasa, 2022)
The use of the Arabic Pad application is very useful for activities in religion, especially all activities in the Prosperity Council of the Jami Darul Hikmah Mosque, Depok where many activities require writing in Arabic and are very difficult things in non-Arabic windows. One of the advantages of this Arabic Pad is that it is a freeware application where the developer of this application is Ebta Setiawan on May 25, 2007 version 1.00 is the first version with rapid development in the following years. Without any installation and is a lightweight application, making this application very popular. At this community service, it is hoped that participants will gain useful knowledge for activities at the Jami Darul Hikmah Mosque Prosperity Council, Depok.